Impact of Chronic Total Occlusion in a Noninfarct-related Artery on Clinical Outcomes in Patients With Acute ST-elevation Myocardial Infarction Undergoing Primary Percutaneous Coronary Intervention. Issue 2 (January 2016) - Zhang, Hui-Ping; Zhao, Ying; Li, Hui; Tang, Guo-Dong; Ai, Hu; Zheng, Nai-Xin; Liu, Jing-Hua; Sun, Fu-Cheng
Abstract : Abstract: In the setting of primary percutaneous coronary intervention (PCI), encountering with chronic total occlusion (CTO) in a noninfarct-related artery (IRA) is not a rare situation. Limited information on the impact of CTO on clinical outcomes in acute ST-elevation myocardial infarction (STEMI) patients undergoing primary PCI has raised more concerns. The aim of the present study was to evaluate the effect of concurrent CTO in a non-IRA on the clinical outcomes in patients with STEMI undergoing primary PCI. In the present prospective study, 555 consecutive patients with STEMI who underwent early primary PCI from January 2010 to December 2013 were included. The patients were divided into 2 groups: no CTO and CTO. Data on 12 months follow-up was obtained from 449 patients. The primary endpoint was the composite of hospitalization from angina, reinfarction, heart failure, or re-revascularization, and cardiac death at 12 months follow-up. Of the 555 patients, 75 (13.5%) had CTO in a non-IRA. Compared with patients in no CTO group, more patients in CTO group had hypertension (62.7% vs 46.5%, P  = 0.009), diabetes (49.3% vs 35.0%, P  = 0.024), and 3-vessel disease (52.0% vs 32.3%, P  = 0.001). Patients with CTO had a lower left ventricular ejection fraction (LVEF) (40.1% ± 16.8% vs 54.3% ± 12.1%, P  = 0.038), more presented with cardiogenic shock on admission (13.3% vs 4.8%, P  = 0.008), compared with patients without CTO. Complete revascularization (CR) was less achieved in CTO group than in no CTO group (33.3% vs 49.1%, P  = 0.013). The 12-month cardiac mortality rate was 14.5% versus 6.2% ( P  = 0.039), the incidence of 12-month primary endpoint was 38.7% versus 21.2% ( P  = 0.003) for CTO and no CTO group, respectively. Multivariate analysis revealed that after correction for baseline differences, CTO in a non-IRA (hazard ratio 4.183, 95% confidence interval 1.940–6.019, P  = 0.001), cardiogenic shock on admission (hazard ratio 3.286, 95% confidence interval 1.097–9.845, P  = 0.034), and 3-vessel disease (hazard ratio 2.678, 95% confidence interval 1.221–5.874, P  = 0.014) remained an independent predictor of 1-year cardiac mortality in patients with STEMI undergoing primary PCI. CTO in a non-IRA in patients with STEMI undergoing primary PCI is associated with a poor prognosis. The presence of CTO in a non-IRA, cardiogenic shock on admission and 3-vessel disease might be an independent risk factor for greater 1-year cardiac mortality in patients with acute STEMI undergoing primary PCI.